Exact Solution for Non-Newtonian Fluid Flow Beyond a Contaminated Fluid Sphere - KUNCHE, Vijaya Lakshmi; MEDURI, Phani Kumar (Engineering Transactions, 2022)
Stokes flow of non-Newtonian fluid beyond a partially contaminated non-Newtonian fluid sphere with interfacial slip condition is considered. An analytic solution for the flow fields indicated by the stream function and the drag force over the sphere was obtained. Special well-known cases are reduced. It was observed that with an increase in slip parameter values, there is a rise in drag coefficient values.